The relationship between serum uric acid levels and severity of addiction in individuals with substance use disorders - Turan, Çetin; Ünal, Süheyla (The European Research Journal, 2023)
Objectives: The aim of this study was to compare serum uric acid levels in patients with methamphetamine and synthetic cannabinoid use disorders pre- and post-detoxification treatment with healthy controls. Secondly, to determine the relationship between the serum uric acid levels of the cases and the severity of the addiction. Methods: Fifty methamphetamine, 50 synthetic cannabinoids, and 40 healthy controls were evaluated on the specified dates. Venous blood samples were taken from the participants to measure serum uric acid and creatinine levels. The arrangement was made by taking the Uric acid/creatinine ratio to neutralize the confounding effect of kidney functions. The Addiction Profile Index was applied to determine the severity of substance abuse in the case group. Results: A statistically significant difference was found between the uric acid values of all three groups when the One-way ANOVA test was performed (p < 0.001). UA values were significantly lower in the case groups than in the healthy control group. When the substance use characteristics of the case groups were compared, a statistically significant difference was found in the duration of substance use (p < 0.010) and motivation (p = 0.031) subtests. Duration of substance use and craving were higher in the synthetic substance group, and motivation was higher in the methamphetamine group. According to the Pearson analysis, the severity of addiction was deduced not to be correlated with serum uric acid and uric acid/creatinine levels in both case groups. Conclusions: Serum uric acid and uric acid/creatinine levels were found to be statistically significantly lower in individuals with methamphetamine and synthetic cannabinoid exposure compared to healthy controls. In this study, it was thought that the lower uric acid levels in the case group compared to the control group may be due to the use of uric acid as an antioxidant or a decrease in purinergic transformation. Future studies may focus on making this distinction.